Meneguhkan Kembali Argumen Kesamaan dan Kesatuan (Esoterik) Agama-agama - Media Zainul Bahri (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2007)
Throughout history, valid and representative arguments discussing the unity and oneness (esoteric) of religions have often referred to perennial philosophy or Sophia perennis. Indeed, through this philosophy, plural religions find commonalities and points of convergence while acknowledging their differences. In this article, the author attempts to present other arguments that further affirm the esoteric unity of religions. These arguments include the theory of continuity of revelation and prophecy, the concept of monotheism present in various religions, the understanding of the existence of one God, albeit appearing in many names, and the mystical perspective (Sufism) in Islam, which strongly supports the notion of the unity (esoteric) of religions.